Community Structure of Periphyton on Seagrass Beds (Enhalus acoroides) in the Waters of Balikpapan Bay, East Kalimantan - Arfina Shariani; Jailani, Jailani; Nurfadilah, Nurfadilah (Faculty of Fisheries and Marine Science, Mulawarman University, 2023)
Periphyton are animals or plants that live below the surface of the water, attached to rocks, twigs, soil or other substrates. Periphyton which is classified into the animal group generally consists of protozoa and rotifers, while periphyton which is classified as plant consists of microalgae. The purpose of this study was to determine the structure of seagrass and the role of the Periphyton community. Measurement of water quality parameters was carried out at the Water Quality Laboratory, Faculty of Fisheries and Marine Sciences, while substrate research was carried out at the Soil Laboratory, Faculty of Agriculture. This research was conducted from November to March 2023 using the quadratic transect method while determining the stations and observation points using the purposive sampling method. Observation locations were determined based on seagrass density and using the transect method with a 50×50 cm quadrant. data were analyzed by calculating the Periphyton Community Structure. The abundance of periphyton in the Bay of Balikpapan, East Kalimantan, consists of seven classes, namely Bacillariophyceae, Ulvophyceae, Mediophyceae, Copepoda, Gastropods, Diplopoda, Dinophyceae. while the highest abundance was at station 3 of 36.1667. The high abundance of Periphyton at station 3 was caused by the sandy substrate and good water quality parameters. Based on the Diversity Index value indicates low Index status, Uniformity Index value indicates low Index status, Dominance Index value indicates low Index status.